USING GUESSING GAME WITH KAHOOT APPLICATION TO IMPROVE CHILDREN VOCABULARY MASTERY - Nur Farisda; Muthmainnah Mursidin; Sitti Nurjannah (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2025)
This study aimed to examine the effectiveness of using a guessing game through the Kahoot application to improve vocabulary mastery among kindergarten children. The research was conducted at TK Dharma Wanita UNHAS, involving children from group B2 as participants. The study employed a pre-experimental design using a one-group pre-test and post-test model. The vocabulary materials covered in this study focused on four main themes: colors, animals, fruits, and numbers. These topics were selected based on their relevance and familiarity to early childhood learners. The pre-test results showed that most students were in the